Service quality analysis of two of the largest retail chains with minimart concept in Indonesia - Hendy Tannady; Filscha Nurprihatin; Hendy Hartono (Verslas: Teorija ir praktika / Business: Theory and Practice, 2018)
Service quality is important because it makes prices more affordable, and also fulfils customer satisfaction. This bolsters trust for customers, and thereby encourages them to keep buying products at retail stores. This research uses Quality Service Analysis method to understand the gap between customers' expectations regarding service attributes and their perceived satisfaction level. This study also uses the method of Importance and Performance Analysis to determine an attribute's category. Therefore, it can determine which priorities should be reinforced to improve customer satisfaction. Through SERVQUAL analysis, there are 10 known attributes of each retailer that has the highest gap score. Through IPA analysis, we know that Alfamart has 7 attributes which warrant serious attention from management. This is due to the high expectations of customers on the indicator, and the fact that the management has not managed well. Meanwhile, Indomaret has 9 attributes that warrant serious attention from management.
Keywords: L81; O14; 650; service quality; importance and performance analysis; retailer; customers; customer satisfaction; satisfaction level